Majelis Rakyat Papua dan Pemberdayaan Orang Asli Papua - Usman Pakasi (Jurnal Jaffray, 2009)
The objective of this research is to find out theoretical understanding about role of Papua Council in empowering local people. The studyconducted thoroughly by using qualitative mechod and phenomenologic strategy. The location of this research is based on the object its material where the institution located, namely in Jayapura city. The empiric obrained through interview technique, observation, and other secondary data.The result of research shows that Papua People Council is the cultural representation of the indigenous peple of Papua that consist of traditionalpeople, women and religion. This institution plays role in keeping the interest and protecting Papua people's righrs by doing supervision upongovernment policy. The empowerment of local people specially related ro tradisional people, women and religion. The empowerment related to the economy, social, culture, politic, and law. The empowerment intended to give the advantage for the prosperity and the sense of justice for the indigenous people of Papua in development.